2003
DOI: 10.1002/ajmg.a.20450
|View full text |Cite
|
Sign up to set email alerts
|

Two cousins with partial trisomy 12q and monosomy 12p recombinants of a familial pericentric inversion of the chromosome 12

Abstract: Partial trisomy 12q and monosomy 12p lead to multiple malformation syndromes. Instead of trisomy 12q that has been reported as a clinically identifiable syndrome, monosomy 12p is characterized by a wide phenotypic spectrum. We report two cousins suffering from severe mental retardation, seizures, and dysmorphic features related to a trisomy 12q24.3-->qter and a monosomy 12p13-->pter resulting from a familial pericentric inversion of chromosome 12. In an attempt to improve the clinical delineation of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…qter region, due to segregation of a parental balanced translocation [Lagier-Tourenne et al, 2004]. To our knowledge, only a few patients with pure 12q duplications have been described [Harrod et al, 1980;Ieshima et al, 1984;Dixon et al, 1993;Houfflin et al, 1993;El-Shanti et al, 1997;Ireland et al, 2004].…”
Section: Introductionmentioning
confidence: 91%
“…qter region, due to segregation of a parental balanced translocation [Lagier-Tourenne et al, 2004]. To our knowledge, only a few patients with pure 12q duplications have been described [Harrod et al, 1980;Ieshima et al, 1984;Dixon et al, 1993;Houfflin et al, 1993;El-Shanti et al, 1997;Ireland et al, 2004].…”
Section: Introductionmentioning
confidence: 91%
“…Many cases of recombinant progeny from pericentric inversion carriers have been reported in the literature (Ishii et al, 1997;Mejia-Baltodano et al, 1997;Goodman et al, 1999;Angle et al, 2000;Dufke et al, 2000;Ilgin Ruhi et al, 2001;Lazzaro et al, 2001;Battaglia et al, 2002;Garcia-Heras and Martin, 2002;Lagier-Tourenne et al, 2004). The viability of the recombinant products mostly depends on the genetic content (and so the size) of the noninverted segment because they are the potential regions to be deleted or duplicated by recombination.…”
Section: Inversion Carriers' Progenymentioning
confidence: 99%
“…The current patient displayed eight of these 17 features. Lagier-Tourenne et al (2004) reported on two patients with monosomy 12p and trisomy 12q, who presented with ataxia. Interestingly, the spasticity, deafness and behavioural problems of our patient have not been described before in patients with a 12q duplication.…”
Section: Discussionmentioning
confidence: 98%